2022
DOI: 10.1007/s11120-022-00905-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary donor triplet states of Photosystem I and II studied by Q-band pulse ENDOR spectroscopy

Abstract: The photoexcited triplet state of the “primary donors” in the two photosystems of oxygenic photosynthesis has been investigated by means of electron-nuclear double resonance (ENDOR) at Q-band (34 GHz). The data obtained represent the first set of 1H hyperfine coupling tensors of the 3P700 triplet state in PSI and expand the existing data set for 3P680. We achieved an extensive assignment of the observed electron-nuclear hyperfine coupling constants (hfcs) corresponding to the methine α-protons and the methyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…5,24,27−31 The Chl molecules responsible for this triplet delocalization have not been clearly identified yet, although the possibility of P D1 , P D2 , Chl D2 , and even Pheo D1 has been suggested. 5,15,19,24,27,30,31 In this study, we identified the Chl molecules on which the triplet state is distributed in PSII by means of FTIR different spectroscopy in combination with site-directed mutagenesis in Synechocystis sp. PCC 6803.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5,24,27−31 The Chl molecules responsible for this triplet delocalization have not been clearly identified yet, although the possibility of P D1 , P D2 , Chl D2 , and even Pheo D1 has been suggested. 5,15,19,24,27,30,31 In this study, we identified the Chl molecules on which the triplet state is distributed in PSII by means of FTIR different spectroscopy in combination with site-directed mutagenesis in Synechocystis sp. PCC 6803.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electron paramagnetic resonance and ENDOR have been used extensively in photosynthesis research since radicals, radical pairs and also triplet states are created in the light-induced single electron transfer that can ideally be investigated by these techniques [131][132][133][134][135][136] even in solution at physiological temperatures [137]. EPR on transition metals like manganese requires, however, cryogenic temperatures due to fast relaxation causing severe line broadening at higher temperatures.…”
Section: Epr Spectroscopy Applied To Psii and The Oecmentioning
confidence: 99%
“…These angular parameters allow us to precisely determine the orientation of ZFS axes in the molecular frame: a rotation of 8 • with respect to the axis passing through the methine groups has been found(see Figure 4C). Assignment of the ZFS tensor directions in the molecular frame is an important task to be fulfilled for exploiting the full potential of orientation-selective triplet-state EPR techniques [77,78]. As a further result, fixing the ZFS directions, this leads to a final orientation of the Q y TDM axes in the Chl a monomers, which translated to MeTHF and EtOH:MeOH mixture gives a deviation of 12 • and 3 • from the molecular y axis, respectively.…”
Section: Solventmentioning
confidence: 99%
“…As a further result, fixing the ZFS directions, this leads to a final orientation of the Q y TDM axes in the Chl a monomers, which translated to MeTHF and EtOH:MeOH mixture gives a deviation of 12 • and 3 • from the molecular y axis, respectively. The assumption that the ZFS tensor directions are the same in the solvents and in WSCP is based on the fact that the ZFS axes orientations are not particularly affected by the environment, as demonstrated by the comparative ENDOR investigations on 3 Chl a in glassy matrix, in WSCP, as well as in photosynthetic reaction centres [27,46,66,78]. Thus, exploiting the excitonic interaction, we were also able to give the orientation of the Chl a Q y TDM, resulting in it being slightly rotated with respect to the molecular y axis.…”
Section: Solventmentioning
confidence: 99%